Thriving through relationships in sport: The role of the parent-athlete and coach-athlete attachment relationship - Davis, L.; Brown, D. J.; Arnold, R.; Gustafsson, H. (Frontiers in Psychology, 2021)
The aim of this research was to examine whether attachment relationships to significant others, such as to parents and/or sports coaches, enable thriving and competition performance within sport. Two studies employing cross-sectional and prospective designs were carried out across different samples of athletes of varied skill levels and sports. In Study 1, we found athletes` attachment to their sports coach was significantly associated with athlete thriving and mediated by psychological needs satisfaction. Results of Study 2 found that athletes` secure attachment to their mother and/or father positively predicted the experience of thriving at the competition while athletes` insecure attachment did not predict thriving. Furthermore, athletes` attachment to both mother and father did not predict competition performance. Together, these two studies acknowledge the significant role that athletes` secure attachment relationships with parents and coaches play in facilitating thriving in athletes. These findings have significant implications for research and practice.